Women, work and industrial relations in Australia in 2019. (June 2020) - Foley, Meraiah; Williamson, Sue; Mosseri, Sarah
Interest in women's labour force participation, economic security and pay equity received substantial media and public policy attention throughout 2019, largely attributable to the federal election and the Australian Labor Party platform, which included a comprehensive suite of policies aimed at advancing workplace gender equality. Following the Australian Labor Party's unexpected loss at the polls, however, workplace gender equality largely faded from the political agenda. In this annual review, we cover key gender equality indicators in Australia, examine key election promises made by both major parties, discuss the implications of the Royal Commission into Aged Care Quality and Safety for the female-dominated aged care workforce, and provide a gendered analysis on recent debates and developments surrounding the 'future of work' in Australia.